2016
DOI: 10.5007/1980-0037.2016v18n4p411
|View full text |Cite
|
Sign up to set email alerts
|

Influence of saddle height and exercise intensity on pedalling asymmetries in cyclists

Abstract: DOI: http://dx.doi.org/10.5007/1980-0037.2016v18n4p411 Pedaling asymmetries quantified during stationary cycling, when cyclist body positioning and intensity remain unchanged, may not fully reproduce the training and competition situations, in which cyclists experience different intensities and may opt for different saddle positioning aiming at power output optimization. Previous studies showed that torque and power can be asymmetric in cyclists. It is not clear whether changes in saddle height and exercise in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
1
6
0
1
Order By: Relevance
“…Although changes in saddle height have previously been shown to influence the relationship between muscle force and length (Bini et al., 2011; De Vey Metsdagh, 1997; Sanderson & Amoroso, 2009), we found no significant effects on body torque from different saddle heights (Figure 2(a)). Our results are consistent with those of Diefenthaeler et al. (2016) who also observed no effects from saddle height on torque generated or the asymmetry between the lower limbs during cycling.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although changes in saddle height have previously been shown to influence the relationship between muscle force and length (Bini et al., 2011; De Vey Metsdagh, 1997; Sanderson & Amoroso, 2009), we found no significant effects on body torque from different saddle heights (Figure 2(a)). Our results are consistent with those of Diefenthaeler et al. (2016) who also observed no effects from saddle height on torque generated or the asymmetry between the lower limbs during cycling.…”
Section: Discussionsupporting
confidence: 93%
“…The choice of this height was based on an ideal pedal performance (Peveler, 2008) and as the safest position to prevent injuries (Wanich et al., 2007). The conditions were then set for the “upward position” (saddle at the reference position + 2.5%) and “downward position” (saddle at the reference position − 2.5%; Diefenthaeler et al., 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main alterations in geometry which appear to affect physiological and biomechanical parameters are related to changes in seat tube angle 6,7 , crank length 8 , and saddle height [9][10][11][12][13][14][15][16][17] . Studies have reported divergent results regarding changes in saddle height.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that pedaling asymmetry changes systematically with crank torque output and exercise intensity [6]. The results demonstrate that pedaling asymmetry in trained road cyclists can be consistent across different saddle heights and even at different cycling intensities [7]. Smak et al conclude that pedaling asymmetry is highly variable ORIGINAL ARTICLE among subjects and that individual subjects may exhibit different systematic changes in asymmetry with pedaling rate depending on the quantity of interest [8].…”
mentioning
confidence: 93%